Performance management system in educational institution using Management by Objectives (MBO) and 360° appraisal method - Shrestha, Gopal (Shanti Journal, 2022)
Performance management is the management activity through which an institution ensures that employees are working effectively and efficiently towards achievement of institutional goal. To ensure that, performance appraisal i.e. evaluating employee’s current or past performance relative to the standard set by institution, is carried on. The data obtained from appraisal is used to take decision of promotion, salary, training and development and for other purposes too. The appraisal is generally done using different appraisal methods or tools like graphic rating method, essay method, critical incident method MBO, 360° appraisal method etc. MBO is now one of the most used a popular tool which is used as appraisal tool, motivational technique as well as planning and control device. Likewise, 360 degree appraisal method is another popular method which is gaining popularity nowadays where all round feedback is taken from all the staffs around the staff going to be appraised. Whatever the method is used, if the appraisal is carried on properly by minimizing common problems like biasness, unclear standards, halo effects etc., any institution can achieve goal through motivated staff with good working environment.